Design, preparation, and in vitro evaluation of gastroretentive floating matrix tablet of mitiglinide - Patel, Meenakshi; Shelke, Santosh; Surti, Naazneen; Panzade, Prabhakar; Al-Keridis, Lamya Ahmed; Upadhyay, Tarun Kumar; Alshammari, Nawaf; Saeed, Mohd (Frontiers in Pharmacology, 2023)
The present research was focussed on the development of floating matrix tablet to prolong the gastric residence time of mitiglinide in order to maintain the level of drug in the blood for improved treatment of type II diabetes mellitus. Tablets were prepared using polymers HPMC K15M and sodium alginate by direct compression technique. Full 32 full factorial design was adopted to optimize the developed formulations. Compatibility between drug and excipients was assessed by FTIR. The tablets were evaluated for different parameters such as hardness, friability, drug content, floating time, in vitro dissolution, stability study etc. Dissolution data was analysed by various kinetic models to ascertain mechanism of drug release. Finally, radiographic study was conducted to estimate the retention time of the optimized floating matrix tablets of MTG inside the body. Results revealed that all the physical properties were within limit. Formulation M3 was optimized based on the desirability value. Besides, optimized M3 formulation displayed stability for six months as evident from miserable changes in drug release pattern and other physical properties. Moreover, Radiographic examination indicated that the tablets remained afloat in gastric fluid for up to 12 h in the rabbitstomach. Therefore, improved drug efficacy and patient compliance may be obtained in patients with type-II diabetis.